(untitled) (Bangladesh Journal of Animal Science, 2013)
Data on morphometrics and performance of 106 Black Bengal goats were collected through an in-depth monitoring survey conducted in 73 families of Gangatia, Borachala and Pachpai villages of Bhaluka Upazila, Mymensingh, Bangladesh using a structured questionnaire. Analyses of variance were performed using the General Linear Model (GLM) procedure under Statistical Package for the Social Sciences (SPSS) version 14.0. Differences between mean values were separated using Duncuns Multiple Range Test (DMRT). Body weight of goats significantly (p<0.001) differed with age classes and body condition scores. Average body weight of Black Bengal goat was 14.47±0.48 kg. Body length at was 46.01±0.66 cm. Chest girth significantly (p<0.001) differed with age classes and body condition scores. Average chest girth of Black Bengal goat was 56.10±0.60 cm. Wither height significantly (p<0.001) differed with age classes and body size. Average wither height of Black Bengal goat was 46.41±0.36 cm. Scrotal length and scrotal circumference did not significantly (p>0.05) differ with age classes, villages and body condition. The number of services needed for each conception of Solid Black, Toggenburg pattern and Brown Bezoar goats were 1.32±0.31, 1.08±0.22, 1.25±0.31, 1.01±0.26 and 1.23±0.27, respectively. The lowest kidding interval was observed in Borachala village (169.80±38.11 days) and in Solid Black goats (176.71±36.17 days). The highest litter size was found in does (1.68±0.39) of Gangatia village (1.67±0.51) and in Solid Black goats (1.67±0.54). The lowest abortion rate was found in Solid Black goats (6.14%). The lowest kid mortality was observed in Solid Black goats (10.00%). Variation observed in morphometric and production traits of indigenous Black Bengal goats indicated an opportunity for their improvement through an in-situ pure breeding program. DOI: http://dx.doi.org/10.3329/bjas.v41i2.14122 Bang. J. Anim. Sci. 2012. 41 (2): 83-89